Video-assisted thoracic surgery for pleuroperitoneal communication - Shota Mitsuboshi; Hideyuki Maeda; Masato Kanzaki (Surgical Case Reports)
Abstract Background Hydrothorax due to pleuroperitoneal communication (PPC) is a rare complication of continuous ambulatory peritoneal dialysis (CAPD). Approximately 50% of the patients need to convert to hemodialysis. Case presentation A 65-year-old man with chronic renal failure due to membranoproliferative glomerulonephritis underwent CAPD. Seven months after starting CAPD, a chest X-ray showed a right hydrothorax. For performing radioscintigraphy, 99mTc-macro-aggregated albumin was administered into the peritoneal cavity with dialysate, and a leakage point of the dialysate into the right pleural cavity was detected. He was diagnosed with PPC and underwent video-assisted thoracic surgery (VATS). The hole was closed by direct suturing and reinforced by a pedicled latissimus dorsi muscle flap (LDM). The patient resumed CAPD 7 weeks later and had no recurrence of the right hydrothorax. Conclusions VATS was a useful method for treating PPC. A pedicled LDM flap is an effective material for preventing the recurrence of PPC.